Synthesis, structure, DNA/protein binding, molecular docking and in vitro anticancer activity of two Schiff base coordinated copper(II) complexes. (1st October 2019) - Manna, Subal Chandra; Mistri, Soumen; Patra, Apu; Mahish, Manas Kumar; Saren, Dama; Manne, Rajesh Kumar; Santra, Manas Kumar; Zangrando, Ennio; Puschmann, Horst
Graphical abstract: Binding interaction of two copper complexes with DNA and bovine serum albumin has been investigated and supported by using molecular docking tool. One complex shows a higher binding affinity exhibiting in vitro moderate growth suppression activity against human breast (MCF7) cancer cell line (= 24 ± 6.24 μM). Abstract: Two Schiff bases HL and HL′, having potential tridentate O, N, N′ donor sets, have been used for the synthesis of two copper(II) complexes, namely [Cu(HL)(pdc)]2 (1 ) and [Cu(L′)2 ]2 (2′ ), where HL = 2-([2-(piperazin-yl)ethylimino]methyl)phenol, pdc = py-2, 5-dicarboxylate and HL′ = 2-(((2-(di-isopropylamino)ethyl)imino)methyl)phenol. X-ray single crystal analysis of complex1 shows a centro-symmetric dimer. It crystallizes with a number of lattice water molecules that form a network of H-bonds, also involving the protonated piperazinium fragment, giving rise to a 3D supramolecular architecture. Complex2′ also crystallizes as dinuclear, formed through mutual bridging phenol oxygen atoms as [Cu(L′)2 ]2, whilst an ESI mass spectrometry study evidences that in solution the complex exists as mononuclear [Cu(L′)2 ] (2 ). The interaction of complexes1 and2 with calf thymus DNA (CT-DNA) and with bovine serum albumin (BSA) was investigated using electronic absorption and fluorescence spectroscopic techniques. In both studies the results show a higher binding affinity of complex1 in comparison to2 . The anticancer activity of the complexes against human breast (MCF7) cancer cell lines reveals that complex1 has moderate growth suppression activity against these cells with an IC50 value of 24 ± 6.24 μM.